IDENTIFIKASI KERAGAMAN GENETIK KENTANG SUPEJOHN TRANSGENIK (Solanum tuberosum L. var supejohn) - Lengkong, Christine L.W.; Polii-Mandang, Jeany; Lengkong, Edy F. (Universitas Sam Ratulangi, 2012)
ABSTRACT The aim of this study was to determine the genetic diversity of potato Supejohn transgenic that had been twenty-five times subcultured with exploration method. The genetic variability was calculated using molecular marker Polimorphic Random Amplified DNA (RAPD) analysis of ten samples from four weeks planlets of Supejohn transgenic plants using ten random primers. DNA isolation of 10 samples using CTAB buffer then measurement of the DNA qualification and quantification, afterwards amplification of DNA by PCR using 10 random primers followed by electrophoresis on a 1% agarose gel with TAE 1x electrode buffer solution. Visualisation the results used UV Transluminator to see DNA bands and the data of polymorphic bands had been analized used the NTSYS-pc version of 1.07 program to obtain the similarity coefficient and the dendrogram.The results showed that five random primers produced polymorphic DNA bands with 0.39 - 0.88 similarity coefficient and the average similarity coefficient is 0.63 (63%) or the genetic diversity of the samples as many as 37%. Dendrogram formed eight distinct clusters corresponding similarity coefficient, the formation of clusters means that there is genetic diversity among the DNA samples. Keywords: potato Supejohn transgenic, RAPD, genetic diversity ABSTRAK Penelitian ini bertujuan untuk menentukan keragaman genetik kentang Supejohn transgenik yang telah dua puluh lima kali disubkultur dengan menggunakan metode penelitian eksplorasi dengan penanda molekuler Random Amplified Polimorphic DNA (RAPD) terhadap 10 sampel tanaman Supejohn transgenik, berumur empat minggu dan menggunakan 10 primer random. Isolasi DNA dari 10 sampel menggunakan buffer CTAB sesudah itu dilakukan pengukuran kualitas dan kuantitas DNA, kemudian dilanjutkan dengan amplifikasi DNA secara PCR menggunakan 10 primer random diikuti dengan elektroforesis pada gel agarose 1% dengan larutan penyanggah elektroda TAE 1x. Visualisasi hasil elektroforesis menggunakan UV Transluminator untuk melihat pita DNA dan analisis data pita polimorfik menggunakan program NTSYS-pc versi 1.07 sehingga didapatkan koefisien kesamaan dan dendrogram. Hasil penelitian menunjukkan bahwa lima primer random menghasilkan pita DNA polimorfik dengan koefisien kesamaan 0.39 – 0.88 dan rata-rata koefisien kesamaan yaitu 0.63 (63%) atau keragaman genetik sampel sebesar 37%. Dendrogram membentuk delapan cluster yang berbeda sesuai koefisien kesamaan,terbentuknya clusters mengartikan bahwa ada keragaman genetik antar sampel DNA. Eugenia Volume 18 No. 3 Desember 2012 Kata kunci : kentang Supejohn transgenik , RAPD, keragaman genetik